Determination of the Best Controlled-Release Potassium Chloride and Fulvic Acid Rates for an Optimum Cotton Yield and Soil Available Potassium - Geng, Jibiao; Yang, Xiuyi; Huo, Xianqi; Chen, Jianqiu; Lei, Shutong; Li, Hui; Lang, Ying; Liu, Qianjin (Frontiers in Plant Science, 2020)
Abstract Potassium and fulvic acid (FA) fertilizer application are two important measures for improving cotton growth. However, there are few studies on the interact application effect of the controlled-release potassium (CRK) in combination with the FA in cotton production. To explore the effects of CRK combined with FA on cotton, two consecutive years of field experiments were conducted in 2018 and 2019 using a split-plot design. The main plots were assigned to two types of potassium fertilizer, controlled-release potassium chloride (CRK) and potassium sulfate (KS), while low, moderate and high FA application rates (90, 180 and 270 kg ha Overall, the FA180 treatment resulted in better cotton growth than that in the FA90 and FA270 treatments. In addition, the release period of CRK in the field during the growth period of cotton was longer than that detected by 25°C static water extraction, which increased the soil available potassium content and met the potassium demands over the whole cotton growth period. Therefore, the application of CRK in combination with 180 kg ha -1 FA is the best choice for cotton fertilization.2